The ethics of hospitality: Jacques Derrida on Unconditional and Conditional Hospitality - Κακολύρης Γεράσιμος (The Greek Review of Social Research, 2013)
Gerasimos Kakoliris’ text focuses on the ethics of hospitality with particular reference to Jacques Derrida’s notion of hospitality. For Derrida, the logic of the concept of hospitality is conditioned by an absolute antinomy or aporia. On the one hand, the law of “real” or “absolute” hospitality demands the unconditional reception of the foreigner. On the other hand, there are the conditional laws of hospitality which, while they translate the unconditional law into a reciprocal right to receive and a duty to offer hospitality, simultaneously impose conditions on it. The relationship between these two elements is then seen to determine the boundaries of any decision to offer hospitality. Against the rather problematic guiding concept of “unconditional” hospitality, Kakoliris counterproposes a continuous, incessant effort of limiting violence towards the arriving foreigner.